How does the health status of older migrants compare to the Canadian and Australian-born population? - Kariuki, Mary (My University, 2021)
Background: Despite Australia's and Canada's rich migration history and the well-known challenges posed by an ageing heterogenous migrant population, little attention has been paid to the health of older migrants in research, policy and practice. Aims and methods: My thesis investigated the variations in the health status of older migrants and their host population and its subsequent determinants using three study designs: systematic literature review (Australia, Canada); serial cross-sectional analyses of a combined dataset (Dynamic Analyses to Optimise Ageing (DYNOPTA), Australia); longitudinal analysis of a DYNOPTA contributory study (Household Income and Labour Dynamics in Australia Study (HILDA)). Findings: In general, the systematic review found older migrants reported an objective health advantage for some non-communicable diseases, but a disadvantage for infectious diseases and poor mental health relative to the older Australian and Canadian-born population. Health (dis)advantages varied by region/country of birth, age, sex and migrating circumstances. With regards to self-reported health, neither the systematic review nor the repeated cross- sectional analysis found convincing differences using binary country of birth. However, using region of birth sub-groups the systematic review and longitudinal analysis demonstrated a self-rated health advantage in North-West Europeans and a self-rated health disadvantage in Southern and Eastern Europeans - both of relevant magnitude. Longitudinally, being older, divorced or never married, current or former smoker and first, native or preferred language other than English were associated with poor health. Higher education attainment, alcohol consumption and being female were associated with better self-rated health. Language, education and increasing age showed a "dose-dependent" association with self-reported health. Conclusions: My findings provide evidence that older migrants with cumulative education and language disadvantages - both potentially remediable - experience poorer self-rated health. In addition to economic integration, policies should address these issues with regard to their impact on health literacy and health inequalities, which persist and magnify as the migrant becomes older.
Keywords: Health and wellbeing; International comparison; Migration and settlement